Wi-Fi Networks are Underutilized - Raghavendra, Ramya; Padhye, Jitu; Mahajan, Ratul; Belding, Elizabeth (2009)
Much of wireless research today focuses on improving capacity of wireless networks. While wireless capacity can be a critical issue in cases where the number of users is large, or for high bandwidth applications such as video downloads, we find that this is not the case in day-to-day environments such as corporate WLANs, universities, homes, cafe's etc. Through empirical measurements in each of these networks, we show that even at peak usage, wireless networks have plenty of spare capacity. For the range of networks that we measured, we found medium utilization remains under 50% for upto 90% of the time. The traffic patterns are bursty, and utilization can reach as much as 80% in some cases on very short timescales, but for most part, there is plenty of capacity available. Ironically, we find that while capacity is plentiful, packet loss remains a problem. Our measurements show that these wireless links on an average suffer from loss rates of about 10%. We discuss the causes and implications of these observations, and consider how our results might guide protocol design.